1923 Cal. Stat. 696, § 1 - (:unkn) unknown (My University, 1923)
Prohibited the manufacture, importation, keeping for sale, offering or exposing for sale, giving, lending, or possession of any instrument or weapon commonly known as a blackjack, slungshot, billy, sandclub, sandbag, metal knuckles, and the concealed carrying of any dirk or dagger. Punishable by imprisonment for 1-5 years.
Keywords: TRANSFER, MANUFACTURE & POSSESSION - NON-GUN ARMS; CARRY - CONCEALED - NON-GUN ARMS